OPTIMIZING SPORTS PERFORMANCE THROUGH MENTAL TOUGHNESS: PILOT STUDY - Răzvan KALININ; Robert BALAZSI; Iacob HANŢIU (Cluj University Press, 2020)
Background. Mental toughness is one of the most important and well-known psychological constructs in sports and beyond. Researchers in the field, argue that the development of mental toughness is based on both the influences of the environment in which the person operates and the learning and training processes that it went through them. "Gold Medal - Metal Training" it's a program for developing mental toughness and it's based on the work of several psychologists and coaches from Eastern Europe and Scandinavia. Aims. The aim of the present study was to verify the 4 essential aspects (process, resources, management and scientific) of the intervention program. Methods. The sample of this study consisted of N = 16 participants (31.8% male and 68.8% female), from a diverse range of sports (Judo, Hockey, Basketball, Triathlon, Dance, Athletics). Of these, 8 are performance athletes, and 8 are amateurs. Their age ranged from 19 to 44 years with a mean of M = 25.81 (SD = 7.70). Self-reports were obtained from all athletes regarding their mental toughness (Mental toughness Inventory) and the feasibility of the intervention program through a questionnaire in accordance with the objectives of the study. Results. Regarding the difference between statistical test indicate significant difference for item 2, item 3 and item 9. For the difference between the level of physical activity statistical test indicate significant difference for item 2. The results obtained in the ANOVA analysis with repeated measurements F (1, 15) = 8.257 (p = 0.012, MSE = 5.181, η² = 0.355) the F test is statistically significant despite the small sample size because the value of Eta (η²) far exceeds the threshold (> 0.14) in terms of a large effect. Conclusions. According to the results, the study is feasible with slight changes related to the implementation and organization of the process, so the coordinator must be more active in collaborating with subjects and provide them with information and suggestions more often. REZUMAT. Optimizarea performanței sportive prin intermediul conceptului Mental Toughness: studiu pilot. Introducere. Mental toughness (MT) este unul dintre cele mai importante și bine cunoscute constructe psihologice în sport și nu numai. Cercetătorii din domeniu susțin că dezvoltarea Mental toughness se bazează atât pe influențele mediului în care acționează persoana respectivă, cât și pe procesele de învățare și formare pe care le-a parcurs. "Medalia de aur - antrenament mental" este un program pentru dezvoltarea Mental toughness și se bazează pe munca mai multor psihologi și antrenori din Europa de Est și Scandinavia. Obiective. Scopul acestei lucrări a fost de a verifica cele 4 aspecte esențiale (proces, resurse, management și științific) ale programului de intervenție. Metode. Eșantionul acestui studiu a fost format din N = 16 participanți (31,8% bărbați și 68,8% femei), dintr-o gamă variată de sporturi (judo, hochei, baschet, triatlon, dans, atletism). Dintre aceștia, 8 sunt sportivi de performanță, iar 8 sunt amatori. Vârsta acestora a variat între 19 și 44 de ani, cu o medie de M = 25,81 (SD = 7,70). Aceștia au completat 2 chestionare, primul cu scopul de a măsura nivelul Mental toughness (Inventarul Mental toughness), iar al doi-lea fiind un chestionar care viza fezabilitatea programului de intervenție în conformitate cu obiectivele studiului. Rezultate. În ceea ce privește genul subiecților testul statistic a arătat diferențe semnificative pentru itemul 2, itemul 3 și itemul 9. Pentru diferența dintre nivelul de practicare a activității fizice testul statistic indicați diferența semnificativă pentru itemul 2. Pe baza rezultatelor obținute în cadrul analizei ANOVA cu măsurători repetate F (1 , 15) = 8,257 (p = 0,012, MSE = 5,181, η² = 0,355) testul F este semnificativ statistic în ciuda dimensiunii reduse a eșantionului, deoarece valoarea Eta (η²) depășește cu mult pragul (> 0,14) în ceea ce privește un efect mare. Concluzii. Conform rezultatelor, studiul este fezabil cu modificări ușoare legate de implementarea și organizarea procesului, astfel încât coordonatorul trebuie să fie mai activ în colaborarea cu subiecții și să le ofere informații și sugestii mai des. Cuvinte cheie: Mental toughness, program Mental toughness, performanță sportivă, studiu pilot, Medalia de aur - antrenament mental, Inventarul Mental toughness.